Atomic force microscopy study of the growth mechnism of gibbsite crystals - Freij, Sawsan; Parkinson, Gordon; Reyhani, Manijeh (Royal Society Chemistry, 2004)
A combination of atomic force microscopy (AFM) and scanning electron microscopy (SEM) has been used to investigate the crystal growth mechanism of gibbsite (aluminium trihydroxide) in pure solutions. Under the conditions studied, the growth on the basal face of synthetic gibbsite prepared from sodium aluminate solution proceeds by a continuous birth and spread mechanism. The nuclei formed on the surface of the basal face of gibbsite grow both laterally and vertically, with lateral growth being much faster than vertical growth. Moreover, a remarkable cyclical, smooth→rough→smooth→rough process has been directly observed. The effect of alkali ions on the crystal growth of gibbsite has been investigated. Curved features and a growth hillock were observed for the first time on the basal face of gibbsite prepared from potassium aluminate solution; whereas, steps terminating within the plane and hexagonal shaped features tilted at an angle and related to the symmetry of the face were imaged on the basal faces of gibbsite prepared from sodium aluminate solution. The results suggest faster growth on the basal face of gibbsite prepared from potassium aluminate compared to that prepared from sodium aluminate, leading to the observed elongated morphology.